Transformasi Pelaporan Keuangan Puskesmas Sarwodadi menuju BLUD Profesional dan Berkelanjutan - Andri Widianto; Yeni Priatna Sari; Hetika Hetika; Destiana Artanti (Universitas Muhammadiyah Semarang, 2025)
In their role as primary healthcare providers, community health centers (Puskesmas) face various challenges in their financial management. The transition to Regional Public Service Agency (BLUD) status offers significant financial flexibility but demands professionalism. This community service program aims to provide mentoring and capacity building to financial managers at the Sarwodadi Community Health Center (Puskesmas) in preparing professional and sustainable BLUD financial reports. The approach used was a coaching clinic, attended by 10 Sarwodadi Community Health Center employees. This approach provided intensive guidance and hands-on practice in preparing BLUD financial reports. The effectiveness of the activity was measured through a comparative analysis of results before and after the community service program. The results showed an increase in participants' understanding of financial reporting. The majority of participants who previously struggled were now able to produce accurate BLUD financial reports. In conclusion, this activity was highly effective in improving the capacity of Puskesmas financial managers, demonstrating that the coaching clinic is a relevant method in supporting the transformation of Puskesmas into transparent, accountable, and professional BLUDs.